UTILIZACIÓN DEL ACRÍLICO DENTAL (metil metacrilato) COMO BARRA ESTABILIZADORA-CONECTORA PARA REDUCCIONES CERRADAS EN FRACTURAS DE TIBIA/PERONÉ O RADIO/CÚBITO EN CANINOS - Cavero A., Francisco (2005)
The methyl metracrilate (mmc) is an acrylic resin used in molds for the manufacture of dental prothesis and may have the function of connective stabilizing bar in the reduction of bone fractures, allowing the insertion of pins in diffent planes. The objective of the present research was to demonstrate that the mmc may work like a external skeletal locking device to fix bone fractures, away from the fracture focus, and therefore, avoiding much of the usual complications observed when other techniques are used. A closed fracture reduction was performed in 10 dogs, with ages varying froms 5 months and 7 years that presented a fracture in the tibia, the fibula, the ulna or the radius bones. All animals were intervened and X rayed every 16 days until the extraction of the external fixation was done on the 6th week post surgery. The recovery of the fracture line was obtained as well as an adequate osteosynthesis that allowed the bone recuperation.